2019
DOI: 10.3126/tujm.v6i0.26583
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Lactamases Production in Multi-drug Resistant Acinetobacter species Isolated from Different Clinical Specimens

Abstract: Objectives: To determine the prevalence of Acinetobacter spp. from different clinical specimens and detect different types of β-lactamase enzymes. Methods: Different clinical samples were collected and 125 Acinetobacter spp. were isolated.  Various biochemical tests were carried out to speciate the Acinetobacter spp. The antibiotic susceptibility pattern and β-lactamase enzymes like Extended spectrum β-lactamase (ESBL), Metallo β-lactamase (MBL) and AmpC β-lactamase were determined. Results: Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In our study, all three types of -lactamases -AmpC, KPC, and ESBL -were produced by 3.8% of isolates. According to the results of other study, 1.78% of the isolates produced all three types of -lactamases (23).…”
Section: Discussionmentioning
confidence: 77%
“…In our study, all three types of -lactamases -AmpC, KPC, and ESBL -were produced by 3.8% of isolates. According to the results of other study, 1.78% of the isolates produced all three types of -lactamases (23).…”
Section: Discussionmentioning
confidence: 77%
“…In our study, all three types of β -lactamases—AmpC, KPC, and ESBL—were produced by 3.8% of isolates. According to the results of other research, carried out in in a tertiary care hospital of South India, 1.78% of the isolates produced all three types of β -lactamases [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of A. baumannii was 21.11% (19/90) in this study which is similar to some previous studies reported from Nepal [36,37] . As the pathogen can endure dry conditions for a long time, they persist in the hospital environment and are responsible for opportunistic infections [17] . Hence, the highest number of isolates were isolated from in-patients (84.2%) which is following other studies [38,49] .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of carbapenem resistance in Acinetobacter in UK, USA, Singapore, Chile, Korea, Portugal, India, and Pakistan was 47-77%, 48%, 50%, 70%, 92%, 85%, 40% and 62-100%, respectively [41][42][43][44][45][46] . The development of resistance in A. baumannii may be due to the presence of wide array 𝛽 -lactamases that hydrolyze and confer resistance to penicillins, cephalosporins, and carbapenems [17] . Resistance to carbapenem is facilitated by resistance mechanisms including enzymatic inactivation, active efflux of drugs, and modification of target sites [47] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation